The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1399-5448.2010.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of glucose intolerance in racially mixed children with cystic fibrosis

Abstract: The low prevalence of carbohydrate intolerance in this population is probably a result of their young age. Another possibility is the low frequency of the ΔF508 mutation. Although not conclusive, these data suggest that in addition to age, the genotype:phenotype ratio may influence the development of glucose intolerance in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…43,44 In populations with low prevalence of ΔF508, such as in Brazil, CFRD is less common. 45 There appears to be a small subgroup with adult onset and a milder form of CF, with a low prevalence of CFRD. Gilljam et al 46 in Toronto reported 7% of their adult patients to be in this group.…”
Section: Geneticsmentioning
confidence: 99%
“…43,44 In populations with low prevalence of ΔF508, such as in Brazil, CFRD is less common. 45 There appears to be a small subgroup with adult onset and a milder form of CF, with a low prevalence of CFRD. Gilljam et al 46 in Toronto reported 7% of their adult patients to be in this group.…”
Section: Geneticsmentioning
confidence: 99%
“…A previous paper, in this cohort, reporting on the carbohydrate aspects of CF was recently published. [7] This cross-sectional study was conducted between August and September 2009. All 46 patients, aged between 6 and 16 years and 2 months, followed at a reference service for CF were selected.…”
Section: Methodsmentioning
confidence: 99%
“…[56] The mechanisms postulated to explain this disturbance are: diet rich in carbohydrates and poor in fats, diabetes, liver disease, elevation of pro-inflammatory cytokines and use of corticosteroids, probably all acting in a combined manner. [57] Recently, lung transplantation was described as being associated with hyperlipidemia in CF patients, probably related to cyclosporine use. [8]…”
Section: Introductionmentioning
confidence: 99%